AS VÁRIAS FORMAS ORGANIZACIONAIS DE ATUAÇÃO EM RESPONSABILIDADE SOCIAL CORPORATIVA E SEUS IMPACTOS INTERNOS NAS ORGANIZAÇÕES OS GRANDES BANCOS NO BRASIL - Guimarães Filho, Arnaldo de Jesus (2008)
This work aims at disseminating research on the internal impacts of various organizational forms of action in Corporate Social Responsibility (CSR) of the main Banks established in Brazil. It also aims at identifying the principal motivating factors of the banks acting in this area. The focus of this work is to verify if existing literature on the subject confirms the internal effects on the company, in its various forms of action, and has as its principal objective the identification of the advantages and disadvantages of each alternative, aiming at defining with more objectivity the most effective and efficient way for companies to act with CSR. Therefore, we researched the development of the CSR movement in Brazil. We identified the specific participation of the banking sector in the movements or CSR and the reasons for banks to join and maintain investments in social causes. Today the commitment to actions of social responsibility is not enough. It is necessary to combine the commitment with business management. Irresponsible or unethical business practices lead to the deterioration of living conditions on the planet and of all life forms, and also puts the sustainability of the company at risk. CSR is much more than donations or financing social projects. In this context an economic sector often criticized - banks - has stood out. Study of this sector is important because of its economic force, potential investment and reach and especially because it is a segment which can be a creator and multiplier of successful social practices.